Analytical treatment of fractional Swift-Hohenberg equation with uncertainty - Amit Kumar; Samaresh Kumbhakar; Shreya Mukherjee (Computational Algorithms and Numerical Dimensions)
In this article, we present the time-fractional Swift-Hohenberg equation (FSFE) with uncertainty where the fractional deriative is chossen in caputo sense. We have solved the fuzzy FSFE by homotopy analysis elzaki transform method (HAETM) which is a collaboration of homotopy analysis method with elzaki transform.The proposed algorithm provides a fast convergence series solution. Three dimensional plots of the solutions, error graphs and h-cut graphs are given to illustrate the efficacy of the method to solve FSFE.